Teaching English as a Foreign Language at Madrasah: A Literature Review - Nuraini Nuraini (Institute of Information Technology and Social Science (IITSS), 2022)
Abstract English is one of the compulsory subjects studied by students of Islamic junior high schools (madrasah tsanawiyah). Madrasah Tsanawiyah is equivalent to junior high school. Although students of Madrasah Tsanawiyah have been studying English since elementary school for several years, many students cannot achieve the desired communicative level. This happens because teaching English in a foreign context to Madrasah Tsanawiyah students is not an easy thing to do. However, it seems that English teachers struggle to teach their students effectively. Many challenging situations in EFL classes at Madrasah affect learning and teaching. English teachers have limited time to teach and students have very limited English learning goals. Some challenges faced by English teachers in Madrasah include curriculum, textbooks, qualified teachers, lack of support, and affective administration. The purpose of this paper is to discuss the challenges of teaching English in Madrasah Tsanawiyah including challenges in teaching English at school, types of challenges in teaching English, and previously related research.